비주얼 커뮤니케이션의 맥락에서 탐색한 3차원 타이포그래피의 시공간적 활용에 관한 연구: 3차원 타이포그래피 프로젝트 연작 〈수사적 공간〉을 중심으로 - 김나무(Namoo Kim) (한국콘텐츠학회 논문지, 20(8), 2020)
The purpose of this study is to deal with practical investigation, which blends symbolism on spatio-temporal level-especially typography in three-dimensional environment-and the symbolism of written language in the context of visual communication. Up until now, typography research and education have mainly been centered on two-dimensional environment and printing technology, such as the paper. However, this study is the result of this researcher's direct design and implementation of projects on typography aside from paper. Accordingly, this study is to provide an opportunity to raise the level of reason and expression used in visual communication to a new level and to expand its scope. To ensure the efficient progress of the project, this study was to identify the structure, system, and process of communication first. Furthermore, this study was to investigate two-dimensional and three-dimensional typography as the backbone of visual communication. In addition, several representative 3D typography works are analyzed in context and used as the conceptual framework of the project conducted for this study. Based on these results, this research verifies and suggests the possibility practically and objectively by creating the project series entitled Rhetorical Space in 3D typography. In addition, this research gives an opportunity to visualize ideas aimed at the development of character-based visual language and visual communication design in the realm of the more spatial, physical, and three-dimensional public environment. 본 연구는 비주얼 커뮤니케이션의 맥락에서 타이포그래피-특히 3차원 환경의 타이포그래피-와 글말의 기호성(記號性)을 시공간의 차원에서 융합하는 실천적 탐구를 다룬다. 지금까지의 타이포그래피 연구와 교육은 주로 지면(紙面)과 같은 2차원 환경과 인쇄 기술을 중심으로 이루어져 왔다. 그러나 본 연구는 지면을 벗어난 타이포그래피에 관한 프로젝트를 연구자가 직접 설계하고 수행한 결과로써 비주얼 커뮤니케이션에 쓰이는 사유와 표현의 수준을 한 차원 높이고 그 범위를 확장하는 기회를 제공한다. 프로젝트의 효율적인 진행을 위해 먼저 커뮤니케이션의 구조와 체계, 프로세스를 파악하고 비주얼 커뮤니케이션의 중추로서 2차원과 3차원 타이포그래피에 대해 고찰한다. 더불어 대표적인 3차원 타이포그래피 작품을 맥락적으로 분석하여 본 연구를 위해 진행한 프로젝트의 개념적 뼈대로 삼는다. 또한 이를 바탕으로 3차원 타이포그래피 프로젝트 연작 <수사적 공간>을 창작하여 그 가능성을 실제적이고 객관적으로 검증하고 제안한다. 나아가 문자 기반의 시각 언어와 비주얼 커뮤니케이션 디자인의 발전을 목표로 하는 아이디어의 시각화를 보다 공간적, 물리적, 그리고 입체적인 공적 환경의 영역에서 발현할 수 있는 기회로 삼고자 한다.